Effect of steamed sago and golden snail flour as substitution of yellow corn on performance of male duck of Alabio, Mojosari and MA - Subhan, Ahmad; Yuwanta, T; Sidadolog, J.Hp; Rohaeni, E.S (Indonesian Journal of Animal and Veterinary Sciences, 2010)
This study was aimed at finding out the effects of combining steaming sago (Metroxylon Spp) and golden snail flourÂ  (Pomacea Spp) as the source of energy in duck ration, substituting yellow corn,Â  on the performance ofÂ  male Alabio, Mojosari, and their cross (MA). One hundred and ninety two young male ducks from the three breeds of 7 days old were assigned in 48 units of cage (4 ducks/cage). Research method applied was Completely Randomized Design with factorial pattern (3x4). The first factor was duck breeds (a) consisted of tree duck breeds: Alabio duck, Mojosari duck and Raja duck and the second factor was types of ration: R0 (control/100% basal ration), R1 (basal ration + 13% steaming sago and 2% golden snail flour), R2 (basal ration + 26% steaming sago and 4% golden snail flour) and R3 (basal ration + 39% steaming sago and 6% golden snail flour). All treatments were repeated four times. The observed variables were performance of ducks: body weight, body weight gain, ration consumption and ration conversion. Results indicated that breed had significant effect (P < 0.05) on body weight, body weight gain and ration conversion. Meanwhile, ration had significant effect (P < 0.05) on ration consumption, body weight gain, and final body weight. It is concluded that the combination of steaming sago and golden snail flour up to 45% of the ration could replace the need for yellow corn as the source of energy in the ration without affecting the performance of male ducks of 1 â 8 weeks old. Cross male ducks were better than that male Alabio ducks and Mojosari because they were more efficient in converting ration into meat which resulted in higher body weight gain. Key words: Steaming Sago, Golden Snail Flour, Male Ducks, Performance